The visuomotor synchronization immersive virtual reality of a depression avatar in a stigma context experience mobilizes the fronto-parietal cortex and anterior insula - dos Santos Kawata, Kelssy Hitomi; Lem, Wey Guan; Ono, Koki; Oyama, Hiroshi (Frontiers in Behavioral Neuroscience, 2025)
IntroductionThe gradual synchronization of the movement of one’s real hand with a virtual one can effectively induce a sense of embodiment (SoE) with an avatar with depression. Although neuroimaging studies have explored the neural correlates of some SoE subcomponents of visuomotor synchronization, the neural correlates of individual differences in SoE and how humans acquire virtual body representations through SoE subcomponents remain to be investigated.MethodsHere, we used the right hand of a virtual patient with depression in immersive virtual reality (IVR) to induce SoE in participants and measured whole brain activity using functional magnetic resonance imaging (fMRI). Participants were instructed to listen to the audio recording of the IVR experience and visualize movements during the fMRI scan. fMRI data were acquired before and immediately after the visuomotor synchronization IVR experience (target condition) or an asynchronized video experience (control condition), followed by embodiment measures related to the two types of experiences.ResultsAll five subcomponents of SoE (sense of ownership, sense of agency, sense of localization, appearance, and response to stimuli) were significantly increased during the visuomotor synchronization IVR experience compared with the asynchronized video experience. A significant negative effect of the SoE score was identified in the frontoparietal and anterior insula only for the visuomotor synchronization IVR experience of guiding the virtual right hand of the avatar with depression, implicating interoceptive and multisensory integration.DiscussionWe demonstrated that all five subcomponents of the SoE were present, and that decreased activity in the frontoparietal and anterior insula were crucial brain regions for the virtual human body to be perceived as one’s own body and promote conscious feelings of embodiment.